Metode Supervisi Behavior - Aap Siti Ulyani; Agus Gunawan; Enung Nugraha (PT PUBLIKASI INSPIRASI INDONESIA, 2023)
The behavioral supervision model refers to a framework that focuses attention on the behavior or actions seen in teaching activities. Behavioral supervision aims to provide constructive guidance to educators so they are able to develop more effective teaching skills. This research is qualitative research with a literature study approach. The research design used by researchers is a descriptive research design. Data were analyzed using interactive model analysis. Miles and Huberman said that this model analysis consists of three components, namely data reduction, data presentation and conclusion drawing, carried out in an interactive form through a cyclical data collection process. Data sources, both primary and secondary, are obtained from books and journals related to supervised behavior. Behavioral Supervision emphasizes the importance of direct observation of teacher actions and behavior in the teaching context. This helps identify strengths and weaknesses that can be improved. This supervision process not only recognizes deficiencies, but provides constructive feedback. The focus is on helping teachers improve their teaching skills and strategies. Behavior Supervision is directed at teacher professional development. Teachers are encouraged to engage in self-development activities to improve the quality of their teaching.